Analysis of the Impact of the Type of Sampling of Representative Properties on the Results of Mass Appraisal - Gnat Sebastian (Folia Oeconomica Stetinensia, 2020)
Research background: Mass valuation is a process in which many properties are valued simultaneously with a uniform approach. An example of a procedure used for mass real estate valuation is the Szczecin Algorithm of Real Estate Mass Appraisal (SAREMA), which can be developed into a multiple regression model. The algorithm is based on a set of drawn representative properties. This set determines, inter alia, the quality of obtained valuations.